Sustainability of the Organizational Changes in the Context of Global Economic Crisis - Armenia Androniceanu; Irina-Virginia Drăgulănescu (Amfiteatru Economic Journal, 2012)
In recent years, as a result of the hastening economic crisis, the Romanian business environment has known important changes. This paper presents and analyzes the changes caused by globalization in small and medium enterprises that exports goods and services from Bucharest. The purpose of the research was to discover the impact of global crisis upon the concerned group of enterprises and the organizational changes implemented by them. Through the research we succeeded to identify the main problems that occurred in the target group enterprises in the context of global economic crisis and what caused the reduction in their developing rhythm. Another part of the paper contains an analysis of the managers perceptions regarding the governmental anti-crisis measures and strategic and tactical changes initiated by them as a natural need to adapt to the particularities of the internal and international business environment. The final part includes the conclusions of the research and a sum of recommendations for efficient management of organizational changes in target group enterprises, with the possibility of generalizing them to all Romanian small and medium enterprises.
Keywords: E32; L21; M2; 330; organizational change; sustainability; globalization; global crisis